Issues of Verse Theory: Aesthetic Categories and the Poetic Text - Grinbaum, Oleg (Respectus Philologicus, 2014)
This article discusses issues of verse theory as it relates to the stanza as a structural unit of a poetic text. The basic aesthetic categories (limits, harmony, grace, and beauty) are considered from the position of mathematical aesthetics, and a mathematical interpretation is offered for three of them (limits, harmony, and grace) in respect to the poetic text (stanza). The category “beauty” cannot correlate with formal descriptions, as far as beauty is the highest subjective-qualitative assessment of an observed object and formed on the basis of a quantitative-qualitative assessment of its limits, harmony, and grace. From the standpoint of aesthetic science, a verse represents the motion limits of a poetic thought. For the mathematical two new formal parameters are introduced, namely the “harmony” and “grace” of the poetic rhythm. In fact, these formal parameters are indicative correlates of expressive (sensual-meaningful) possibilities and kinds of artistic and poetic form (stanzas). In the network of mathematical aesthetics, new parameters acquire clear and mathematically precise definitions and computational procedures that make it possible to quantitatively assess the harmonic potential of different stanzas in their structural-systemic representation. The concept of a stanza’s harmonic profile is introduced, which allows very subtle differences to be captured in the aesthetic properties of different stanzas of Russian classical verse. The employment of new parameters is demonstrated through examples of the most productive of Pushkin’s stanzas.
Keywords: Poetic Text; Stanza; Mathematical Aesthetics; Harmony; Grace; The “Golden Section”